Principes coextensifs de la fiction sérielle, de la distribution diffusée à une pratique interprétative dialogique : une nouvelle donne socio-narrative ? - Céline Masoni Lacroix; Bruno Cailler (Cahiers de Narratologie)
This text aims at exploring television and web forms of serial writing. The dichotomy between production and reception will be overtaken in the crossing of industrial and narrative logics to the dialogical dimension underlying the co-construction of stories, identities and meaning. Our analysis is built upon a socioeconomic approach of cultural industries and a socio-narrative approach of fiction stories and narrative contents production made for and by the audience. On-line reading and writing practices question production and serial (re)creation principles and bring a sense to interactivity uses. Transmediality appears to be the place where concurrency and complementarity of iteration process or serial formula and narrative transformation can be understood.